Real-time multimedia using progress web application - Amirah Adlina Amran (Nanyang Technological University, 2021)
Modern society are always more interested to get their hands on new innovative technology and application. While the development of native mobile applications have an advantage because of the wide range of user experience, the evolution of Progressive Web Applications (PWAs) has also gained more attention in the recent years due to their robustness and efficiency in its features, which works just like a native mobile application. With the ongoing pandemic, users spend more time on their mobile phones, and some are also using their time to enrol in web developing courses. In this report, I am going to go through the process of developing a progressive web application that allows users to fetch real-time multimedia data between peers, with the integration of WebRTC, JavaScript and Socket.IO. The structure includes planning of possible features of a native app, to developing and executing the application with the objective to create a progressive web using APIs such as RTCPeerConnection, RTCDataChannel and MediaStream in WebRTC.